Peningkatan Literasi Digital Guru SMA melalui Pelatihan Pengembangan Asesmen Pembelajaran Bahasa Inggris Berbasis Teknologi Abad ke-21 - Basuki Basuki; Nurhidayati Nurhidayati; Yuli Widiyono; Ari Fajar Isbakhi; Siti Wahyuni; Talitha Octavia (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2026)
Digital transformation requires teachers to be more confident in using technology, particularly in designing meaningful assessments for 21st-century learning. This community service program aimed to strengthen the digital literacy of English teachers at SMA Negeri 7 Purworejo through practical training in developing technology-based assessments that support Higher Order Thinking Skills (HOTS) and the 4C skills. The program used a participatory, hands-on approach involving workshops, technical training, mentoring, classroom implementation, and evaluation. Teachers were guided to use Google Forms, Quizizz, Kahoot, and Learning Management Systems to develop interactive assessment instruments suited to English language learning. Pre-tests, post-tests, assessment products, and participant feedback were used to evaluate the program. The activity is expected to improve teachers’ confidence and practical skills in designing and integrating digital assessments into classroom practice, while providing assessment products that can be further developed and used sustainably. Overall, the program offers a practical pathway for strengthening teachers’ digital capacity and encouraging more engaging English language assessment practices.